The Portrayal of Resistance in Rap Lyrics Between Kendrick Lamar and Rich Brian - Zihan Mailan Nisa; Bunyamin Faisal; Agry Pramita (Universitas Islam Negeri Palopo, 2025)
This study discusses the analysis of rap song lyrics using Hippolyte Taine's theory and a comparison of the depiction of resistance and comparison between two rappers with different backgrounds. The purpose of this study is to reveal the cultural differences between Kendrick Lamar and Rich Brian. The method used is qualitative descriptive. The data used are rap song lyrics from each rappers. This study focuses on the analysis of three songs selected from one album from each artist, three songs from Kendrick Lamar's album